Pericarp ontogeny and histochemistry of the exotesta and pseudocaruncle of Euphorbia milii (Euphorbiaceae) - Demarco,Diego (2011)
Abstract Several types of fruit occur in Euphorbiaceae, notably the explosively dehiscent dry fruit, and different seed-coat anatomies with taxonomic importance. This paper aims to describe the pericarp ontogeny and structure in Euphorbia milii Desmoul., and evaluate the presence of the secretory exotesta and caruncle. The fruit is a schizocarp, whose the pericarp development begins with a periclinal division of the inner epidermal cells. The derived cells divide, forming about four layers of obliquely elongated cells. Then, the adjacent parenchyma cells elongate, giving rise to a palisade layer and finally, the cells between this layer and the vascular strands undergo mitosis, originating about four layers of elongated cells perpendicularly to the inner oblique cells. These three zones lignify, while the region between the vascular strands and the exocarp, where idioblasts, hypodermis and laticifers are present do not show significant changes. Before the dehiscence, a lysis of cells of the septa and the desiccation of the fruit occur, which causes contraction of the non-lignified tissues and tension between the lignified zones, promoting rupture of each mericarp from central columella and on the dorsal strand, ejecting the seeds. The seeds have pseudocaruncle and the exotesta secretes mucilage, facilitating their imbibition.